Easy women : sex and gender in modern Mexican fiction - Castillo, Debra A. (University of Minnesota Press, 1998)
Combining early twentieth-century novels, current best-selling pulp fiction, and testimonial narratives, Castillo explores how Mexican writers have positioned the "easy woman" in their works.